Chromatic contrast dependence of reaction time to random‐dot stereograms at isoluminance. Issue 6 (9th September 2015) - Lin, Kai; Liao, Ningfang; Zhao, Dazun; Dong, Shuwen; Li, Yasheng
Abstract: The relationship between reaction time and perceived contrast of random‐dot‐stereograms has been investigated in this article. First, reaction times of random‐dot stereograms with luminance contrast variations and chromatic contrast variations at isoluminance were examined. Further experiments of reaction times were measured for random‐dot stereograms filtered by a two‐dimensional Gaussian filter. The results clearly indicate that reaction time gradually decreases as contrast increases and level outs when contrast approaches to some value. Furthermore, reaction times for same contrast were shorter for luminance changes than the chromatic variations along the red–green axis, which in turn were shorter than those along blue–yellow axis. Therefore, it could be concluded that luminance contrast cues are more effective than chromatic contrast cues at isoluminance in facilitating stereo perception. On the other hand, it has been found that there was no apparent difference of reaction times for filtered random‐dot stereograms, compared with the unfiltered cases. Finally, there are large inter‐subject variations in stereo perception. © 2015 Wiley Periodicals, Inc. Col Res Appl, 41, 564–570, 2016